Heme Oxygenase-1: A Critical Link between Iron Metabolism, Erythropoiesis, and Development - Stuart T. Fraser; Robyn G. Midwinter; Birgit S. Berger; Roland Stocker (Advances in Hematology)
The first mature cells to arise in the developing mammalian embryo belong to the erythroid lineage. This highlights the immediacy of the need for red blood cells during embryogenesis and for survival. Linked with this pressure is the necessity of the embryo to obtain and transport iron, synthesize hemoglobin, and then dispose of the potentially toxic heme via the stress-induced protein heme oxygenase-1 (HO-1, encoded by Hmox1 in the mouse). Null mutation of Hmox1 results in significant embryonic mortality as well as anemia and defective iron recycling. Here, we discuss the interrelated nature of this critical enzyme with iron trafficking, erythroid cell function, and embryonic survival.